Morphometric study of the hepatic lesions experimentally induced in hamsters by Entamoeba dispar and E. histolytica - Costa C.A.X.; Brito K.N.O.; Gomes M.A.; Caliari M.V. (Parasite, 2007)
Evolution of experimental hepatic lesions produced in hamsters with Entamoeba histolytica and E. dispar was evaluated quantitatively and qualitatively through morphometry and immunohistochemistry. Animals infected with E. dispar developed hepatic lesions quantitatively and qualitatively similar to those produced by E. histolytica on the first three days of infection. On the 6th and 8th days of infection, E. histolytica produced larger tissue damage than E. dispar. A gradual decrease was observed in the number of trophozoites along the infection. A negative correlation was observed between the reduced number of trophozoites and the larger area of necrosis in both groups, confirming the importance of trophozoites killed in the lesion genesis. Regarding the genetic similarity between E. histolytica and E. dispar, comparison strategy between lesions produced by these species may culminate in identifying virulence factors of E. histolytica.